Soft wheat to patient of blight genetics of patience (Experimental biology, 2016)
Hard to the patient of blight, sort of bluewheat, educed patience, basic gender 5А (2=12,44) and 2В (2=31,21) in a chromosome, 1В (χ2=8,84**) and 4D (χ2=7,88**;) on chromosomes the basic quality of gender to promote or reduce modifier gender populated turned out. On 2В and chromosomes of 5А sort of bluewheat stationed oneself temporally marked by the symbols of Bt16, Bt17.
Keywords: wheat; blight; allele; gen; modifier; localization; identification.